2013
DOI: 10.1016/j.chemphys.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved high-harmonic spectroscopy of valence electron dynamics

Abstract: Time-Resolved High-Harmonic Spectroscopy (TRHHS) is an emerging technique for probing valence electron dynamics in molecules undergoing photochemical reactions. A general description of the technique including experimental and theoretical aspects is given. The relation of TRHHS to other time-resolved techniques is discussed, with particular emphasis on the specificities of TRHHS. Coherence endows TRHHS with two of its original properties: the interference of excited and unexcited molecules makes it highly sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…Last, a 3D calculation taking into account the evolution of the molecular wavepackets along the three dimensions was performed, assuming constant harmonic dipole moments and phases except for from the I p τ phase. The results hardly show any modulation in the harmonic signal 53 . Since the model neglecting wavepacket motion and taking into account only the population evolutions gave the best qualitative agreement with their experiments, Kraus et al concluded that the experimental signal reflected the variation of the diabatic state populations, the phase modulations I p τ associated to the vibrational motion being quickly washed out by wavepacket spreading in the three dimensions.…”
Section: Discussionmentioning
confidence: 93%
“…Last, a 3D calculation taking into account the evolution of the molecular wavepackets along the three dimensions was performed, assuming constant harmonic dipole moments and phases except for from the I p τ phase. The results hardly show any modulation in the harmonic signal 53 . Since the model neglecting wavepacket motion and taking into account only the population evolutions gave the best qualitative agreement with their experiments, Kraus et al concluded that the experimental signal reflected the variation of the diabatic state populations, the phase modulations I p τ associated to the vibrational motion being quickly washed out by wavepacket spreading in the three dimensions.…”
Section: Discussionmentioning
confidence: 93%
“…1, provides the intensity of the diffracted radiation as an additional observable that complements the intensity of the undiffracted radiation. While the latter has been shown to be formally identical in collinear and transientgrating pump-probe experiments carried out with identical spatially-averaged excitation fractions, [17] the diffracted radiation has an enhanced contrast. Whereas the undiffracted radiation arises from signals of excited and unexcited molecules weighted by their relative populations, the diffracted radiation results from an interference of emissions with equal weights and thus enhanced contrast.…”
Section: Methodsmentioning
confidence: 98%
“…[18] Theoretical models of increasing detail have also been developed and are described in refs. [14,16,17]. The experimental results, through comparisons with the theoretical models, have demonstrated the main principles and sensitivities of TRHHS.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations